A simplified and robust risk stratification model for stem cell transplantation in pediatric acute myeloid leukemia - Yang, Hua; Xun, Yang; Shen, Yali; Wang, Hongtao; Tao, Yu; Wang, Huihan; Zhang, Xinyue; Liu, Rongqiu; Yu, Huarong; Wei, Li; Yan, Jinsong; Zhu, Xiaoyu; et al. (Cell reports. Medicine, 2024)
The efficacy of stem cell transplantation (SCT) in pediatric acute myeloid leukemia (pAML) remains unsatisfactory due to the limitations of existing prognostic models in predicting efficacy and selecting suitable candidates. This study aims to develop a cytomolecular risk stratification-independent prognostic model for SCT in pAML patients at CR1 stage. The pAML SCT model, based on age, KMT2A rearrangement (KMT2A-r), and minimal residual disease at end of course 1 (MRD1), effectively classifies patients into low-, intermediate-, and high-risk groups. We validate the effectiveness in an internal validation cohort and in four external validation cohorts, consisting of different graft sources and donors. Moreover, by incorporating the FMS-like tyrosine kinase 3/internal tandem duplication (FLT3/ITD) allelic ratio, the pAML SCT model is refined, enhancing its ability to effectively select suitable candidates. We develop a simple and robust risk stratification model for pAML patients undergoing SCT, to aid in risk stratification and inform pretransplant decision-making at CR1 stage. [Display omitted] •A simplified and robust prognostic model is developed for SCT in pAML patients at CR1•The model, independent of cytomolecular risk, offers good predictive accuracy•The model shows reliable accuracy across graft sources and donor types•With the FLT3/ITD AR, the model precisely identifies SCT candidates likely to benefit Hua et al. develop a simplified and robust risk stratification model for SCT in pAML patients at CR1 stage. Independent of cytomolecular risk stratification, the model provides reliable predictions across diverse populations, graft sources, and donor types. Incorporating the FLT3/ITD allelic ratio enhances its ability to select suitable candidates.